Bodily synchronization underlying joke telling - Schmidt, R. C.; Nie, Lin; Franco, Alison; Richardson, Michael J. (Frontiers in Human Neuroscience, 2014)
Advances in video and time series analysis have greatly enhanced our ability to study the bodily synchronization that occurs in natural interactions. Past research has demonstrated that the behavioral synchronization involved in social interactions is similar to dynamical synchronization found generically in nature. The present study investigated how the bodily synchronization in a joke telling task is spread across different nested temporal scales. Pairs of participants enacted knock–knock jokes and times series of their bodily activity were recorded. Coherence and relative phase analyses were used to evaluate the synchronization of bodily rhythms for the whole trial as well as at the subsidiary time scales of the whole joke, the setup of the punch line, the two-person exchange and the utterance. The analyses revealed greater than chance entrainment of the joke teller’s and joke responder’s movements at all time scales and that the relative phasing of the teller’s movements led those of the responder at the longer time scales. Moreover, this entrainment was greater when visual information about the partner’s movements was present but was decreased particularly at the shorter time scales when explicit gesturing in telling the joke was performed. In short, the results demonstrate that a complex interpersonal bodily “dance” occurs during structured conversation interactions and that this “dance” is constructed from a set of rhythms associated with the nested behavioral structure of the interaction.